Is Puccinia graminis f.sp. tritici – virulence Ug99 a threat to wheat production in the North West Plain Zone of India?* - NAGARAJAN, S. (Indian Phytopathology, 2012)
North West Plain Zone (NWPZ) is the most important wheat growing area of India and the 10.0 million hectares under wheat is the back-bone of the country’s food security system. Enormous amount of surplus grain is produced in the NWPZ for the nation-wide public distribution system. Any production threat to NWPZ will have serious implications on Indian agriculture and India’s cherished desire to have home grown self-sufficiency in food. Since the appearance of a new virulence of Puccinia graminis f.sp. tritici in Uganda in the year 1999, popularly called as Ug99 was widely publicized as a threat to Indian wheat production and to India’s food security,a detailed epidemiological study on the relevance of Ug99 to the NWPZ of India was conducted. Results presented here shows that Ug99 is not a threat to wheat production in the NWPZ or to India’s food security and the concern hype, is a wrong signal.